(3JPcQI GdfMGIs - (3eMeO Hf jhSa Hf Ydj Hf jhSa GHf nMnqjGf GdZQfGWj GdCfOdSj GdLjGfj, GdpqfraRj, CKjQ GdOjf, CHh MjGf,J (B745 (3g` s
(3ChdgG (B:s
(3QH MQa , NdGaG ddcSGFi hGHf GdWQGhI hef hGabgG ai GOYGA GSejJgG s
(3BNQgG (B:s
(3aHgPG (B[ (3GcJaGA (B] (3GdPi bQQfGg jJe Cf Jchf GdBjI GdecQeI ajgG GSJKfGA ef GSJKfGA hGddg Gdehab ddUhGH s
(3gPG GdLRA ef GdfhGOQ ceG CTGQi GdCSJGP eMeO EHQGgje GdcJGfi ecJHI Ydi GdhQbI GdChdis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B152 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B130s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI HgG CQVg s
Keywords: (3GdfMhs